How to Read the Bible: History, Prophecy, Literature – Why Modern Readers Need to Know the Difference and What It Means for Faith Today – Steven L. McKenzie - Kalve, Peter (Reviews in religion and theology, 2006)
Book reviewed: How to Read the Bible: History, Prophecy, Literature – Why Modern Readers Need to Know the Difference and What It Means for Faith Today, Steven L. McKenzie, Oxford University Press 2005 (0-19-516149-6, 0-19-516149-1), 204 pp., hb $26.00